Main factors of inefficiency of the law of collective labor relations in the Tacna region 2001-2015 - Gordillo Cossio, Mario (2019)
The study has allowed to relate the dependent and independent variables in the social context of an extended period of time to determine their behavior and correlation, raising the objective of determining the degree of inflection between both variables that significantly affect the collective working climate in the city Of Tacna; As well as of obtaining official information and analyzing comparatively the effects and characteristics of compliance with current regulations on collective labor relations in the Tacna region. The scientific method has been used it the inductive-deductive. The type of research is qualitative and the explanatory level of cross-section. As for the design is non-experimental obtaining the information of direct observation. The population of the study is that referred to the city of Tacna taking the sample of trade union organizations in the region to determine the behavior and degree of effectiveness of the standard. The instruments used were the interview and questionnaire. The study concludes that among the independent variables of normativity and weak collective relations there is correlation with the effects that the trade union crisis has had in Peru since the nineties, because the norms that regulate Collective Labor Relations do not promote the adequate exercise of the collective right of workers but their weakening. Regulatory deficiencies have been identified in terms of compliance with the recommendations of the International Labor Organization and the lack of policies to promote collective bargaining at the state level, which has led to direct social and economic consequences for the unionized population and not unionized. The normative change in this matter is there fore of urgent necessity, presenting a first proposal.